2013
DOI: 10.1080/10665684.2013.838126
|View full text |Cite
|
Sign up to set email alerts
|

Muslim American University Students’ Perceptions of Islam and Democracy: Deconstructing the Dichotomy

Abstract: The aftermath of 9/11 and the current surge of revolutions in North Africa and the Middle East have caused Muslim Americans to be either demonized or forgotten altogether, despite the significance of their everyday navigation of both Islamic and democratic values and unique efforts toward identity construction. The neglect of the Muslim American individual experience in the dominant discourse on Islam and democracy has stifled the voices of members of this marginalized population, thereby limiting their self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Similarly, Lamont and Collet's (2013) study of Muslim undergraduates explored political values and identities. In this study, the researchers found issues of peer acceptance of expressible political beliefs: Ultimately, students considered how their words were read by their peers because of being seen as Muslim.…”
Section: Muslim Student Identities In the United Statesmentioning
confidence: 99%
“…Similarly, Lamont and Collet's (2013) study of Muslim undergraduates explored political values and identities. In this study, the researchers found issues of peer acceptance of expressible political beliefs: Ultimately, students considered how their words were read by their peers because of being seen as Muslim.…”
Section: Muslim Student Identities In the United Statesmentioning
confidence: 99%